Irrational use of azithromycin in typhoid endemic areas: A challenge on multidrug-resistant typhoid treatment - Irfan Ullah; Kiran Shafiq Khan; Qasim Mehmood; Muhammad Junaid Tahir; Muhammad Irfan Malik; Ali Ahmed; Muhammad Usman Munir (School of Medicine, Universitas Syiah Kuala, 2021)
Typhoid is a food-borne fatal disease caused by Salmonella typhi. It causes inflammation of the intestine, resulting in diarrhoea, fever, headache, cough, and muscle pain. Improved hygiene has resulted in a marked decline in typhoid fever cases in many developed countries. However, significant typhoid cases emerge in low and middle-income countries annually, including Pakistan. Typhoid fever accounts for a larger percentage of acute febrile illnesses in Pakistan. Azithromycin is the only effective drug used in multidrug-resistant typhoid. The emergence of drug resistance typhoid has been of more significant concern in recent years due to its irrational use of azithromycin. It is considered the last antibiotic to eradicate multidrug-resistant typhoid fever from Pakistan. In this article, we express our concern of the irrational use of azithromycin in Pakistan and its effect on typhoid in the country.